Effectiveness and safety of acupuncture and moxibustion for peripheral facial paralysis: A protocol for an overview of systematic reviews and meta-analysis. Issue 38 (18th September 2020) - Zhou, Xingchen; Xiong, Jun; Chi, Zhenhai; Lu, Lunbin; Chen, Jun; Tang, Genhua; Zhu, Siyuan; Zhong, Zhiying; Guo, Han
Abstract: Background: Peripheral facial paralysis (PFP) seriously affects patients' quality of life and work and even causes psychological problems such as anxiety and depression for them. Acupuncture (ACU) and moxibustion have been widely used to treat the disease with satisfactory results. Several systematic reviews and meta-analyses have reported the effectiveness of acupuncture for patients with PFP. However, the evidence has not been systematically synthesized. This overview aims to synthesize and assess the reliability of evidence generated from these systematic reviews (SRs) and meta-analyses of ACU and moxibustion for PFP. Methods: We will make a comprehensive retrieval in 9 databases as following: (1) Embase; (2) Cochrane Library; (3) Pubmed; (4) Chinese databases SinoMed (previously called the Chinese Biomedical Database); (5) Chinese National Knowledge Infrastructure (CNKI); (6) Chinese Scientific Journals Database (VIP); (7) Wanfang Data (WF). The time is limited from the construction of the library to August 2020. We will use the Assessment of Multiple Systematic Reviews-2 (AMSTAR-2) tool to evaluate methodological quality. Preferred Reporting Items for Systematic Reviews and Meta-analysis Protocols (PRISMA-P) will be used in the report checklist to assess the quality of reports in the study. The Grading of the Classification of Recommendations, Evaluation, Development and Evaluation (GRADE) will be used to evaluate the included SRs and meta-analysis. Our reviewers will conduct systematic reviews, qualification evaluation, data extraction, methodological quality and evidence quality screening in pairs. The outcomes of interest include: the effective rate, the House-Brackmann (H-B) score, cure rate, and side effects. Or any other scale used to assess the level of illness. The evidence will be synthesized where appropriate based on patient subgroups and outcomes. Results: The results will be published in a peer-reviewed journal. Conclusion: This overview will provide comprehensive evidence of ACU and moxibustion for patients with PFP. Trial registration number: INPLASY202080016.